Maxillary edentulous jaw tray with aesthetic forecasting function - WANG JINGRONG; GAO SHANSHAN (2021)
The invention relates to a maxillary edentulous jaw tray with an aesthetics forecasting function, in particular to an edentulous jaw tray which records anterior tooth aesthetics information of a patient when the patient is diagnosed for the first time and provides reference for later tooth arrangement. The maxillary edentulous jaw tray consists of different types of maxillary tray bodies, artificial teeth and mandibular handles; six arranged maxillary anterior teeth are used as handles of the edentulous jaw tray; the tray is selected according to the dental arch size, the face type, the lip shape and the like of the edentulous jaw patient; the size of the tray is divided into three models of large (L), medium (M) and small (S); each model is divided into three grades of 1, 2 and 3; each grade corresponds to different lip side fullness sizes; and the sequence is as follows: 1<2<3. The artificial teeth of each model and grade are divided into three shapes, namely a square shape, an oval shape and a sharp shape